Dilema Keamanan Indonesia dalam Ketegangan Antara Amerika Serikat dan China di Konflik Laut China Selatan - Siti Sarah; Widodo Widodo; Yusnaldi Yusnaldi; Pujo Widodo; Herlina Juni Risma Saragih (Journal of Education on Social Science (JESS), 2022)
The South China Sea is known as the second busiest sea lane in the world after the Suez Canal in Egypt, this area also has an abundance of living creatures and has large oil and natural gas reserves. Because of its potential, the area is still a contest for claims between several countries. Currently, it is known that the United States and China are the largest hegemonic countries in the economic field that are fighting for power in the South China Sea region. Some experts even discussed the possibility of competition that will end with war or military conflict in the 21st century. As a result of this tension, other countries in Southeast Asia which are generally not superpowers have put themselves in a situation that is called a security dilemma. Indonesia is not a claimant country in the South China Sea area but has sovereignty near the area which is Natuna Island. If there is a conflict between the United State and China in the South China Sea area, it will have direct implications for the sovereignty of the Indonesian state in Natuna. To deal with this scenario, Indonesia must prepare its defense forces. In this security dilemma situation, Indonesia is strengthening its military and making alliances with other countries that also do not want conflict or war, Indonesia also trying to balance its power with China and the United States with the balance of power strategy. The aim of this article is to describe whether the balance of power strategy that has been carried out by Indonesia is successful as a deterrence strategy.